2017
DOI: 10.1111/cobi.12887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preference heterogeneity among landowners on spatial conservation prioritization

Abstract: The participation of private landowners in conservation is crucial to efficient biodiversity conservation. This is especially the case in settings where the share of private ownership is large and the economic costs associated with land acquisition are high. We used probit regression analysis and historical participation data to examine the likelihood of participation of Danish forest owners in a voluntary conservation program. We used the results to spatially predict the likelihood of participation of all for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…; Nielsen et al. ). Adapting microtargeting to this particular challenge presents a novel opportunity to prioritize conservation investments by spatially coupling fine‐grain social and ecological data across large extents.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…; Nielsen et al. ). Adapting microtargeting to this particular challenge presents a novel opportunity to prioritize conservation investments by spatially coupling fine‐grain social and ecological data across large extents.…”
Section: Discussionmentioning
confidence: 98%
“…In these contexts, the management of valued resources is directly tied to individual landowner decisions. Previous studies have sought coupled social-ecological landscape prioritizations, recognizing that the likelihood of conservation success is a function of biophysical as well as human dimensions and dynamics (Game et al 2011;Guerrero et al 2013;Karimi et al 2017;Nielsen et al 2017). Adapting microtargeting to this particular challenge presents a novel opportunity to prioritize conservation investments by spatially coupling fine-grain social and ecological data across large extents.…”
Section: Conservation Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…
Eyvindson et al (2017) comment on our recent paper, Nielsen et al (2017), in which we examined the revealed participation choice of Danish forest owners in a voluntary conservation program. We used the results to predict spatially the likelihood of all Danish forest owners participating in such programs and assessed the value of such information.Eyvindson et al acknowledge that the issues we address are important.
…”
mentioning
confidence: 99%